Utilization of a Dynamic Stifle Flexion Apparatus in Preventing Recurrence of Quadriceps Contracture: A Clinical Report - Wilkens, B. E.; McDonald, D. E.; Hulse, D. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Quadriceps contracture is a well documented postoperative complication of femoral fractures, especially in immature animals. Historically, management of this condition has been difficult, and long-term prognosis has usually been poor. This case documents surgical correction of the quad-riceps contracture in a mixed breed dog, and the use of a dynamic stifle flexion apparatus postoperatively. The purpose of the dynamic stifle flexion apparatus was to encourage early, active use of the affected limb by the patient. Concurrent passive flexion and extension exercises, by the owner, were an integral component in preventing recurrence of pathological contracture of the quadriceps muscle group.Quadriceps contracture of the left quadriceps muscle group was diagnosed in a sixteen-week-old mixed breed dog twelve weeks following repair of a femur fracture. Surgical correction of the contracture was undertaken, and a dynamic stifle flexion device was applied to prevent future recurrence of the contracture. Sixteen weeks following repair, function had returned to the limb with stifle and hock ranges of motion approaching the values measured immediately postoperatively.
Keywords: Quadriceps contracture; dynamic stifle flexion device; femur fracture